CAPACITY OF LUIS ALBERTO WARAT'S ENVIRONMENTAL MEDIATION AND ECO-CITIZENSHIP AS A SYNERGY IN CITIZEN (RE) CONSTRUCTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This research aims to highlight Luis Alberto Warat's eco-citizenship as an effective tool to address environmental preservation and transformation from ecology, citizenship, politics and subjectivity through environmental mediation as a way to strengthen democracy. and social inclusion as well as highlighting the need for new perspectives in building a harmonious environment. For Luis Alberto Warat, ecology, citizenship, politics and subjectivity are elements that, having a balance, can reflect in a new perception between man (being) regarding the environment, promoting a transformation in social reality and its challenges. The research uses the deductive method according to the classical understanding, which departs from the general for thematic specificity and the research technique is bibliographic and observational and monographic procedure. From this perspective, Warat's eco-citizenship praises the recognition of the other and his role as a subject in constant evolution with love as a central element in the construction of human relations. Thus, the ecological subject becomes aware of his role and function in the environment where he lives, that is, the preservation and social transformation pass through this subject aware of his transformative role being able to realize new perspectives / alternatives in the search for a constructive socioenvironmental environment and social actors aware of their role in citizen building